Berlin red : an Inspector Pekkala novel of suspense - Eastland, Sam (Eastland, Sam. Inspector Pekkala novel., 2017)
"April, 1945. East of Berlin, the Red Army stands poised to unleash its final assault upon the ruined capital of Hitler's Thousand Year Reich. To the north, at a lonely outpost near the Baltic Sea, German scientists perfect a guidance system for the mighty V2 rocket, which has already caused massive damage to the cities of London and Antwerp. This device, known only by the codename Diamond Stream, will allow the rocket to arrive at its target with pin- point accuracy. So devastating is the potential of this newly-mastered technology that Hitler's promise to the German people of a 'miracle weapon' that will turn the tide of the war might actually come true. When a radio message sent to Hitler's Headquarters, heralding the success of Diamond Stream, is intercepted by an English listening station, British Intelligence orders one of its last agents operating in Berlin to acquire the plans for the device. Desperate to evacuate their agent from the doomed city before the Red Army swarms through its streets, British Special Operations turns to the Kremlin for help. They ask for one man in particular - Inspector Pekkala. This time, for Pekkala, it is personal" -- summary from www.inspectorpekkala.com